БНХАУ-ын ӨМӨЗО-ны эдийн засгийн хөгжилт ба хувийн хэвшлийн аж ахуйн эзлэх байр суурь (Journal of International Studies, 2005)
English title: Republic of China's Inner Mongolian Autonomous territory's economic development and the position of private sector